The FIFA World Cup 2022: Effects on Qatar's Tourism - Tarida Marlin Surya Manurung; Farhan Rafi Ramadhan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explored the impact of the FIFA World Cup 2022 on Qatar's tourism sector, focusing on tourist satisfaction. Using qualitative methods, data were collected from hotel reviews, interviews, and literature reviews. The World Cup significantly boosted short-term tourism, with a notable rise in arrivals as many visitors came specifically for the event and expressed a desire to return due to their positive experiences. Qatar, as the first Arab nation to host such a major sporting event, is expected to celebrate its successful hosting globally, especially within the GCC region. In the long term, Qatar aims to establish itself as a premier sports tourism destination, attracting attention from international sports organizations for future mega-events. The upcoming AFC Asian Cup in early 2024 highlights this ambition. While its tourism development lags behind faster-growing GCC nations like the UAE, Qatar's steady progress indicates potential for growth. Overall, the study concludes that the FIFA World Cup 2022 was a success, with high tourist satisfaction levels laying a strong foundation for Qatar's future tourism opportunities. Keywords: FIFA World Cup 2022, Tourism Sector, Tourist Satisfaction, Sports Tourism